2014
DOI: 10.1038/onc.2014.69
|View full text |Cite
|
Sign up to set email alerts
|

Ahnak functions as a tumor suppressor via modulation of TGFβ/Smad signaling pathway

Abstract: We provide detailed mechanisms of Ahnak-mediated potentiation of transforming growth factor β (TGFβ) signaling, which leads to a negative regulation of cell growth. We show that Smad3 interacts with Ahnak through MH2 domain and that Ahnak stimulates Smad3 localization into nucleus leading to potentiating TGFβ-induced transcriptional activity of R-Smad. Moreover, overexpression of Ahnak resulted in growth retardation and cell cycle arrest through downregulation of c-Myc and cyclin D1/D2. We describe results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 35 publications
7
119
1
1
Order By: Relevance
“…Specifically, nuclear localization of Ahnak in complex with phospho-Smad3 and binding to promoter of c-Myc were strongly enhanced in response to TGF-␤, indicating that Ahnak downregulates the expression of c-Myc as Smad3 target genes. Consistently, Ahnak-deficient MEF cells show a significant up-regulation of c-Myc expression (17).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Specifically, nuclear localization of Ahnak in complex with phospho-Smad3 and binding to promoter of c-Myc were strongly enhanced in response to TGF-␤, indicating that Ahnak downregulates the expression of c-Myc as Smad3 target genes. Consistently, Ahnak-deficient MEF cells show a significant up-regulation of c-Myc expression (17).…”
supporting
confidence: 59%
“…have previously demonstrated that Ahnak plays an inhibitory role in c-Myc expression through TGF␤-Smad3 signaling cascade in epithelial cells (17). To evaluate whether Ahnak regulates c-Myc expression in embryonic fibroblasts, we examined Ahnak knock-out (Ahnak Ϫ/Ϫ ) MEF.…”
Section: Mutually Exclusive Expression Of Ahnak and C-myc-wementioning
confidence: 99%
“…The precise function of PDAP1 is unclear, but it has been reported to be highly up-regulated in the secretome of neoplastic gastric epithelial cells (58), a context in which SMYD2 activity was recently characterized (26). Finally, AHNAK and AHNAK2, which are uniquely and extensively directly mono-methylated by SMYD2, appear to possess diverse functionality (reviewed in (59)) with roles ranging from cell adhesion (60), cell signaling (61,62), and tumor cell migration and invasion (63). Whether the extensive mono-methylation of the AHNAK and AHNAK2 CRUs by SMYD2, as well as the individual sites we identified in other SMYD2 substrates, regulates the function of these and other proteins remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of biotinylated proteins in AsPC-1 cells were identified as putative K-Ras-interacting partners in transfected HEK293T cells. Noteworthy abundant AsPC-1 hits included the giant, putative tumor suppressor protein AHNAK (67), but also multiple cell surface signaling proteins, including EGFR, integrin β1, mucin 13, ephrin and its receptor, and CD44. These results are discussed below.…”
Section: Identification Of Cellular K-ras-interacting Proteinsmentioning
confidence: 99%